Quantitative and qualitative 2D electrophoretic analysis of differentially expressed mitochondrial proteins from five mouse organs. Issue 1 (18th December 2012) - Techritz, Sandra; Lützkendorf, Susanne; Bazant, Esther; Becker, Silke; Klose, Joachim; Schuelke, Markus
<x xml:space="preserve">Abstract</x> Mitochondria fulfill many tissue‐specific functions in cell metabolism. We set out to identify differences in the protein composition of mitochondria from five tissues frequently affected by mitochondrial disorders. The proteome of highly purified mitochondria from five mouse organs was separated by high‐resolution 2DE. Tissue‐specific spots were identified through nano‐LC/ESI‐MS/MS and quantified by densitometry in ten biological replicates. We identified 87 consistently deviating spots representing 48 proteins. The percentage of variant spots ranged between 4.2% and 6.0%; 21 proteins having tissue‐specific isospots. Consistent tissue‐specific processing/regulation was seen for carbamoyl‐phosphate‐synthase, aldehyde‐dehydrogenase 2, ATP‐synthase α‐chain, and isocitrate‐dehydrogenase α‐subunit. Thirty tissue‐specific proteins were associated with mitochondrial disorders in humans. We further identified alcohol‐dehydrogenase, catalase, quinone‐oxidoreductase, cyclophilin‐A, and Upf0317, a potential biotin‐carboxyl‐carrier protein, which had not been annotated as "mitochondrial" in Gene Ontology or MitoCarta databases. Their targeting to the mitochondria was verified by transfection of full‐length GFP‐tagged plasmids. Given the high evolutionary conservation of mitochondrial metabolic pathways, these data further annotate the mitochondrial proteome and advance our understanding of the pathophysiology and tissue‐specificity of symptoms seen in patients with mitochondrial disorders. The generation of 2D electrophoretic maps of the mitochondrial proteome using tissue specimens in the milligram range facilitates this technique for clinical applications and biomarker research.